INFLUENCE OF HEPATOCELLULAR CARCINOMA ETIOLOGY IN THE SURVIVAL AFTER RESECTION - LOPES,Felipe de Lucena Moreira (2016)
ABSTRACT Background: Hepatocellular carcinoma (HCC) is the most frequent type of primary liver cancer and its incidence is increasing around the world in the last decades, making it the third cause of death by cancer in the world. Hepatic resection is one of the most effective treatments for HCC with five-year survival rates from 50-70%, especially for patients with a single nodule and preserved liver function. Some studies have shown a worse prognosis for HCC patients whose etiology is viral. That brings us to the question about the existence of a difference between the various causes of HCC and its prognosis. Aim: To compare the prognosis (overall and disease-free survival at five years) of patients undergoing hepatectomy for the treatment of HCC with respect to various causes of liver disease. Method: Was performed a review of medical records of patients undergoing hepatectomy between 2000 and 2014 for the treatment of HCC. They were divided into groups according to the cause of liver disease, followed by overall and disease-free survival analysis for comparison. Results: There was no statistically significant difference in the outcomes of the groups of patients divided according to the etiology of HCC. Overall and disease-free survival at five years of the patients in this sample were 49.9% and 40.7%, respectively. Conclusion: From the data of this sample, was verified that there was no prognostic differences among the groups of HCC patients of the various etiologies.